Content and bioaccessibility of bioactive compounds with potential benefits for macular health in tiger nut products. (October 2022) - Hernández-Olivas, Ever; Asensio-Grau, Andrea; Calvo-Lerma, Joaquim; García-Hernández, Jorge; Heredia, Ana; Andrés, Ana
Abstract: Clinical studies have associated the consumption of tiger nuts ( Cyperus esculentus L.), and its derivates, with improved macular health, due to the presence of certain liposoluble compounds with antioxidant activity, especially to lutein and zeaxanthin. However, the benefits derived from ingestion of tiger nut products may vary depending on the release of these compounds from the food matrix to the digestive fluids and their eventual bioabsorption. Therefore, this study aims at evaluating the influence of the food matrix on the liberation and final bioaccessibility of bioactive compounds with positive impact on macular health in different tiger nut products (flour, oil, and milk with and without added sucrose). The in vitro digestibility of macronutrients and the release of vitamin E, lutein, zeaxanthin, β-carotene, and total polyphenols of tiger nut products was studied. In addition, the antioxidant activity of the bioaccessible fraction was determined by ABTS, DPPH and FRAP assays. Results showed that tiger nut milk resulted in the greatest proteolysis and total polyphenols bioaccessibility. Moreover, flour can contribute to hypoglycaemia and, alongside oil, were the best sources of carotenoids and vitamin E. Gastrointestinal digestion increased the antioxidant activity of milk, but the addition of sucrose decreased this effect. The food matrix was a highly relevant factor protecting or hindering the digestion and release of bioactive compounds in the digestive environment. Thus, tiger nut products are presented as ingredients with great potential to develop functional foods oriented to macular health. Graphical abstract: Image 1